Power quality enhancement in electricity networks using grid-connected solar and wind based DGs - Matlokotsi, Tlhoriso (Department of Electrical Engineering, 2017)
The integration of DG into utility networks has significantly increased over the past years primarily as a result of growing energy demand, coupled with the environmental impacts posed by conventional fossil fuel-based power generation. The prominent DG technologies which are capable of meeting bulk energy demands and are clean energy sources are wind and solar energy sources. The resources for solar and wind based DG are available in abundance in most geographical locations in South Africa and the rest of Africa. Through the Renewable Energy Independent Power Producer Procurement Programme (REIPPPP) introduced by the South African government in 2011, 3 920 MW of renewable energy has been procured to date. Out of this, solar and wind energy constitute 2 200 MW and 960 MW, respectively. Grid integration of solar and wind-based intermittent DGs may however pose negative impacts on the quality of power supplied by the utility network. Some of the detrimental impacts of DG include voltage fluctuations, flicker, etc. which are in general categorised as power quality (PQ) problems. The proper planning of DG integration is required to mitigate the negative impacts they pose on system's PQ to ensure that the performance of the utility network is enhanced in terms of the overall PQ improvement of the system. This dissertation reviews general PQ problems in utility networks with DG integration and whether poor planning of DG integration affects PQ negatively. The work emphasizes on the impacts of grid integration of wind and solar PV sources on power quality. It investigates the manner in which wind and solar energy systems differ in their impacts and capacity to improve PQ of the network in terms of a number of factors such as point of integration and capacity of DG, type of DG, network loading, etc. The role of grid-integrated DG in PQ improvement in electricity network is also investigated by exploring different PQ improvement techniques. The networks considered for the grid integration of DG for PQ improvement in this work are the IEEE 9-bus sub-transmission network at the nominal voltage of 230kV and the IEEE 33-bus distribution network at the nominal voltage of 12 kV. The aspects essential for facilitating proper planning of DG integration for PQ improvement and total loss reduction are investigated and the comparative analysis is made between grid integration of wind and solar PV based DGs. The simulations of different case studies in this work are done using DIgSILENT PowerFactory version 14.1 as well as coding in MATLAB. The cases studies conducted are aimed at facilitating the proper planning of grid integration of wind and solar PV-based DGs by comparing their PQ improvement capabilities under different scenarios. First the investigation of how their location and capacity affect the network voltage profiles and active power losses is conducted. Their ability to improve the system's PQ is also studied by observing PQ improvement strategies such as voltage control, installation of energy storage and the optimal placement of DGs under different scenarios. In order to account for the weakness of most South African utility grids, PQ improvement in weak networks with DG integration is also studied by investigating how DG integration in networks with different grid strengths affect the system's PQ. The results provide an understanding of the role of grid integration of wind and solar based DGs on PQ which is useful in the planning of grid integration of RE, particularly in South African electricity networks. The results revealed that the location and capacity of integrated DGs indeed affect the quality of power as well as active power losses in the grid. It is also established that a significant improvement in network's PQ and line loss reduction can be achieved in networks with wind and solar integration. The results however indicated that wind and solar PV based DGs differ in their impacts and capacity to improve the quality of power in the network. Furthermore, the results revealed that wind and solar plants integration into weak utility grids may pose adverse impacts on the system's PQ. It was however established that including reactive power control devices such as STATCOM and SVC at the PCC can successfully improve the system's PQ and enable grid code compliance in electricity networks with DG integration.